UPAYA PENINGKATAN MENULIS TEKS PERSUASI MENGGUNAKAN METODE STAD PADA SISWA SMP - Cahyaningsih, Santi; Wikanengsih, Wikanengsih (IKIP Siliwangi, 2019)
The purpose of this study is an effort to improve writing skills of junior high school students in persuasive text material using the STAD method. Writing is an aspect that is used by humans to communicate or convey indirect messages. The research method used by the researcher was the experimental method, with the design of the pre-test one post-test group. The research sample is class VIII junior high school students. Data collection tools used are learning implementation plans, observation sheets and test sheets. The results of the pre test and post test showed an increase in students' writing skills in the persuasion text material using the STAD method. The results of the study can be concluded that there is an increase in students' writing skills in persuasive text material using the STAD method. The results of teacher learning observations in the 85% class were carried out and student learning in the 80% class was carried out. The results of this study indicate an increase in students' writing skills in persuasive text material using STAD and can improve well according to the objectives expected in the study.